A Minimal Test for Convex Games and the Shapley Value - Mark Voorneveld; Sofia Grahn (Uppsala University, Department of Economics, 2001)
A set of necessary and sufficient conditions for convexity of a transferable utility game in terms of its decomposition into unanimity games is shown to be minimal: none of the conditions is redundant. The result is used to provide an axiomatization of the Shapley value on the set of convex games.
urn:nbn:se:uu:diva-2512
Keywords: C71; 330; Convex game; unanimity game; Shapley value; axiomatization; Spieltheorie; Theorie; Shapley-Wert